Gallium-Protoporphyrin IX Inhibits Pseudomonas aeruginosa Growth by Targeting Cytochromes - Hijazi, Sarah; Visca, Paolo; Frangipani, Emanuela (Frontiers in Cellular and Infection Microbiology, 2017)
Pseudomonas aeruginosa is a challenging pathogen due to both innate and acquired resistance to antibiotics. It is capable of causing a variety of infections, including chronic lung infection in cystic fibrosis (CF) patients. Given the importance of iron in bacterial physiology and pathogenicity, iron-uptake and metabolism have become attractive targets for the development of new antibacterial compounds. P. aeruginosa can acquire iron from a variety of sources to fulfill its nutritional requirements both in the environment and in the infected host. The adaptation of P. aeruginosa to heme iron acquisition in the CF lung makes heme utilization pathways a promising target for the development of new anti-Pseudomonas drugs. Gallium [Ga(III)] is an iron mimetic metal which inhibits P. aeruginosa growth by interfering with iron-dependent metabolism. The Ga(III) complex of the heme precursor protoporphyrin IX (GaPPIX) showed enhanced antibacterial activity against several bacterial species, although no inhibitory effect has been reported on P. aeruginosa. Here, we demonstrate that Ga PPIX is indeed capable of inhibiting the growth of clinical P. aeruginosa strains under iron-deplete conditions, as those encountered by bacteria during infection, and that GaPPIX inhibition is reversed by iron. Using P. aeruginosa PAO1 as model organism, we show that GaPPIX enters cells through heme-uptake systems, primarily the PhuR receptor which plays a crucial role in P. aeruginosa adaptation to the CF lung. We also demonstrate that intracellular GaPPIX inhibits the aerobic growth of P. aeruginosa by targeting cytochromes, thus interfering with cellular respiration.